Motives for Keeping Green Mindfulness and Firm Size - Lin, Chieh-Yu; Ho, Yi-Hui; Wu, Young-Long; Yu, I-Chi (Archives of Business Research, 2019)
While integration of environmental concepts and business operations has become a fundamental part of value creation strategy, environmental management has received sustained research interest over time. Organizational green mindfulness is a way of organizational attitude during environmental management marked by preoccupation with failure, reluctance to simplify interpretations, sensitivity to operations, commitment to resilience, and deference to expertise. The study expects that firms should keep mindfulness thinking while engaging in environmental management. The main purpose of this study is to propose a theoretical framework exploring the moderating effect of firm size on the motives for keeping green mindfulness. The motives proposed in the study include economic motive and social motive. Firm size would moderate the influences of economic motive and social motive on keeping green mindfulness.